ON THE CIRCUMSTANCES PRESENTING THE PROFESSIONAL QUALIFICATION OF THE INVESTIGATOR - Solovev, Alksandr (State and Law, 2021)
The article is devoted to some issues of the pre-trial stage, in particular, those related to the legal status of an investigator which presuppose the efficency of this stage. Here the author analyzes the questions concerning the improvement of professional skills of an investigator, realations of the state bodies involved in the criminal procedure, as well as enlargement of the investigator’s procedural independence.
Keywords: investigator; procedural independence of an investigator; initiation of a criminal case; prosecutorial supervision; judicial control